Identification, structure, and characterization of an exopolysaccharide produced by Histophilus somni during biofilm formation - Sandal, Indra (BioMed Central, 2011)
BACKGROUND: Histophilus somni, a gram-negative coccobacillus, is an obligate inhabitant of bovine and ovine mucosal surfaces, and an opportunistic pathogen responsible for respiratory disease and other systemic infections in cattle and sheep. Capsules are important virulence factors for many pathogenic bacteria, but a capsule has not been identified on H. somni. However, H. somni does form a biofilm in vitro and in vivo, and the biofilm matrix of most bacteria consists of a polysaccharide. RESULTS: Following incubation of H. somni under growth-restricting stress conditions, such as during anaerobiosis, stationary phase, or in hypertonic salt, a polysaccharide could be isolated from washed cells or culture supernatant. The polysaccharide was present in large amounts in broth culture sediment after H. somni was grown under low oxygen tension for 4-5 days (conditions favorable to biofilm formation), but not from planktonic cells during log phase growth. Immuno-transmission electron microscopy showed that the polysaccharide was not closely associated with the cell surface, and was of heterogeneous high molecular size by gel electrophoresis, indicating it was an exopolysaccharide (EPS). The EPS was a branched mannose polymer containing some galactose, as determined by structural analysis. The mannose-specific Moringa M lectin and antibodies to the EPS bound to the biofilm matrix, demonstrating that the EPS was a component of the biofilm. The addition of N-acetylneuraminic acid to the growth medium resulted in sialylation of the EPS, and increased biofilm formation. Real-time quantitative reverse transcription-polymerase chain reaction analyses indicated that genes previously identified in a putative polysaccharide locus were upregulated when the bacteria were grown under conditions favorable to a biofilm, compared to planktonic cells. CONCLUSIONS: H. somni is capable of producing a branching, mannose-galactose EPS polymer under growth conditions favorable to the biofilm phase of growth, and the EPS is a component of the biofilm matrix. The EPS can be sialylated in strains with sialyltransferase activity, resulting in enhanced density of the biofilm, and suggesting that EPS and biofilm formation may be important to persistence in the bovine host. The EPS may be critical to virulence if the biofilm state is required for H. somni to persist in systemic sites.